2019
DOI: 10.4102/ajod.v8i0.364
|View full text |Cite
|
Sign up to set email alerts
|

Family-based activity settings of children in a low-income African context

Abstract: Background: There has been an overwhelming call to improve the understanding of how children develop within an African context as Euro-American definitions of competence have been uncritically adopted as the norm for children in Africa. The activities that children engage in within the family setting are seen as important to understand how children develop within context. The use of activity settings is closely aligned with a strengths-based perspective of family-centred practice and contributes to improved su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Within the two Ghanaian studies, caregivers perceived play as a shift away from the child's learning at school and did not understand that play is educational as well 26,30 . Similar perceptions were detected in the study by Balton et al study 25 ; however, in the Lachman et al study, the caregivers viewed play as a form of building relationships and spending time with the child; however, this was hampered by time constraints 27 . These varying perceptions regarding play indicate how play is conceptualised in different contexts and highlights the need to promote understanding of play which will help enhance development.…”
Section: Microsystemsupporting
confidence: 73%
See 3 more Smart Citations
“…Within the two Ghanaian studies, caregivers perceived play as a shift away from the child's learning at school and did not understand that play is educational as well 26,30 . Similar perceptions were detected in the study by Balton et al study 25 ; however, in the Lachman et al study, the caregivers viewed play as a form of building relationships and spending time with the child; however, this was hampered by time constraints 27 . These varying perceptions regarding play indicate how play is conceptualised in different contexts and highlights the need to promote understanding of play which will help enhance development.…”
Section: Microsystemsupporting
confidence: 73%
“…This was additionally observed in the limited understanding of play or activity engagement that was beneficial to the child. In a study by Balton et al 25 , colouring, drawing and pasting were seen as promotive to development; however, this was assumed due to these activities being done at school. Whereas in another study, the children participated in home and self-care tasks, however this was viewed as a means to promote self-reliance, rather than promote developmental skills 28 .…”
Section: Microsystemmentioning
confidence: 99%
See 2 more Smart Citations
“…Behaviour is often viewed by caregivers as what is expected and accepted within their respective communities. The type of behaviour that will maintain a respectful life within the family and community varies within and across various cultures (Balton et al, 2019). A previous study demonstrated that up to 43% of caregivers are concerned about their child’s behaviour, whereas no problems/delays are identified during a formal developmental assessment (Glascoe, 2013).…”
Section: Discussionmentioning
confidence: 99%